TEYL PRINCIPLES IN PRACTICE: A CONTENT ANALYSIS OF PRE-SERVICE TEACHERS’ DIGITAL STORYTELLING VIDEOS - Siti Sopiah (Linguists : Journal of Linguistics and Language Teaching, 2026)
This study investigates how Teaching English to Young Learners (TEYL) principles are represented in digital storytelling videos created by pre-service teachers. Drawing on theories of digital storytelling and TEYL pedagogy, the study aims to examine the extent to which Meaningful Learning, Contextualization, Interaction, Scaffolding, Repetition and Recycling, and Affective Engagement are integrated into digital learning media. A qualitative content analysis was employed to analyze seven digital storytelling videos produced by pre-service teachers within a single instructional context. The videos were selected using purposive sampling based on specific criteria, and the data were analyzed using a coding framework derived from established TEYL principles. The findings reveal an uneven integration of pedagogical principles. Meaningful Learning, Contextualization, and Affective Engagement are consistently implemented at a strong level, indicating that pre-service teachers are able to create engaging and context-rich storytelling. However, Interaction and Scaffolding are weakly represented, with most videos relying on one-way narration and limited instructional support. Repetition is present across videos but is generally used as a narrative feature rather than as a structured learning strategy. Only one video demonstrates a balanced integration of all principles. These findings suggest that pre-service teachers tend to approach digital storytelling as a performance-oriented activity rather than a pedagogically driven instructional tool. The study contributes to the literature by highlighting the gap between the theoretical potential of digital storytelling and its practical implementation in TEYL contexts. It also emphasizes the need for teacher education programs to provide more explicit guidance on integrating pedagogical principles into digital media design.